K.H. SAMANHUDI DAN SJARIKAT DAGANG ISLAM - Muthahharah, Muthahharah (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2015)
This article discusses the history and role of KH. Samanhudi as a founder of the first Islamic organization in the history of Islam. With minimal background experience of the organization, he was able to establish an organization that would later give birth to various heroes Indonesia, the Islamic Trade Union. This organization but aims to promote trade and unite the Muslims, as well as to take the fight against colonial oppression carried out by the Netherlands. The method used in this research is qualitative method by tracking references relating to the relevant figures. The results showed that KH. Samanhudi much affected by the thinkers of the Middle East reformers, like Jamaluddin al-Afghani, Shaykh Muhammad Abduh and Sheikh Muhammad Rida. whereas in the case of organizational thinking, KH. Samanhudi many discussions with the results obtained Journalists First, Raden Mas Tirto Adi Soerjo. With this, KH. Samanhudi gave birth to the idea that quite brilliant in his day to repel the Company of the archipelago, which combines the teachings of Islam and the unity of the Muslims, later with a strong union putting up stiff resistance to uphold social justice for all Indonesian people.